Experimental application of gliders communication system in South China Sea - Shuyang Jia; Shuyang Jia; Shuyang Jia; Baoheng Liu; Baoheng Liu; Sichen Zou; Xiaochuan Zhang; Xiaochuan Zhang; Xiaochuan Zhang (Frontiers in Communications and Networks)
Utilizing the motion characteristics of underwater gliders, a water acoustic communication system based on heterogeneous gliders was designed. The system consists of a surface wave glider and an acoustic underwater glider, which are respectively equipped with ultra-short baseline and acoustic modulation and demodulation devices. Real-time data transmission is performed using underwater acoustic communication equipment. The glider consists of three cabins connected in sequence and is capable of diving to a depth of over 1,000 m. Two acoustic transducers are fixed separately at the bow and stern of the underwater glider to ensure that the energy transmission range and angle remain consistent to the surface wave energy glider even if the glider’s attitude changes. The underwater acoustic communication equipment is installed in the cabin and has a standby power consumption of only 5 mW. To verify the feasibility of this integration method, an offshore test was conducted in the South China Sea. The test results show that the underwater glider can perform reliable acoustic communication over a distance of over 5 km. This study demonstrates the potential wide-ranging applications of acoustic underwater gliders in underwater sound measurement and collaborative networks, etc.